Multimodal depression detection based on an attention graph convolution and transformer - Xiaowen Jia; Jingxia Chen; Kexin Liu; Qian Wang; Jialing He (Mathematical Biosciences and Engineering)
Traditional depression detection methods typically rely on single-modal data, but these approaches are limited by individual differences, noise interference, and emotional fluctuations. To address the low accuracy in single-modal depression detection and the poor fusion of multimodal features from electroencephalogram (EEG) and speech signals, we have proposed a multimodal depression detection model based on EEG and speech signals, named the multi-head attention-GCN_ViT (MHA-GCN_ViT). This approach leverages deep learning techniques, including graph convolutional networks (GCN) and vision transformers (ViT), to effectively extract and fuse the frequency-domain features and spatiotemporal characteristics of EEG signals with the frequency-domain features of speech signals. First, a discrete wavelet transform (DWT) was used to extract wavelet features from 29 channels of EEG signals. These features serve as node attributes for the construction of a feature matrix, calculating the Pearson correlation coefficient between channels, from which an adjacency matrix is constructed to represent the brain network structure. This structure was then fed into a graph convolutional network (GCN) for deep feature learning. A multi-head attention mechanism was introduced to enhance the GCN's capability in representing brain networks. Using a short-time Fourier transform (STFT), we extracted 2D spectral features of EEG signals and mel spectrogram features of speech signals. Both were further processed using a vision transformer (ViT) to obtain deep features. Finally, the multiple features from EEG and speech spectrograms were fused at the decision level for depression classification. A five-fold cross-validation on the MODMA dataset demonstrated the model's accuracy, precision, recall, and F1 score of 89.03%, 90.16%, 89.04%, and 88.83%, respectively, indicating a significant improvement in the performance of multimodal depression detection. Furthermore, MHA-GCN_ViT demonstrated robust performance in depression detection and exhibited broad applicability, with potential for extension to multimodal detection tasks in other psychological and neurological disorders.